Nano-cluster stability following neutron irradiation in MA957 oxide dispersion strengthened material - Ribis, J; Lozano-Perez, S (2014)
ODS steels are promising materials for Sodium cooled Fast Reactors since their fine distribution of nano-clusters confers excellent mechanical properties. However, the nano-feature stability needs to be assessed under neutron irradiation. Before irradiation, the characterizations show that nano-particles are finely distributed within the ferritic matrix and are identified to have a pyrochlore type structure. After irradiation of the MA957 alloy in the Phenix French reactor at 412 C up to 50 dpa and 430 C up to 75 dpa, transmission electron microscopy characterization reveals a very slight density fall but no distinguishable difference in nano-features size before and after irradiation. In addition, after both irradiations, the nano-oxides are still (Y, Ti, O) compounds with orientation relationship with the matrix. A multislice simulation of high resolution images suggests that nano-particles still have a fcc pyrochlore type structure after irradiation. A possible change of lattice parameter seems to be highlighted, possibly due to disordering by cascade effect. © 2013 Elsevier B.V. All rights reserved.